Portable molecular diagnostic instruments in microbiology: current status. (April 2020) - Zidovec Lepej, S.; Poljak, M.
Abstract: Background: Mobile microbiology is an evolving concept that has the potential to reduce morbidity and mortality associated with infectious diseases on a global level. Molecular methods used in the context of mobile microbiology ensure rapid and accurate aetiological diagnostics and allow timely initiation of clinical care. The great majority of published data regarding molecular diagnostics in mobile laboratories have focused on emerging viral infections and using laboratory-developed assays. Use of clinically validated and commercially available molecular diagnostic instruments in routine diagnostics of infectious diseases in mobile laboratories has received only limited attention in the field. Objectives: This review summarizes the suitability of a range of portable diagnostic molecular instruments for application in mobile laboratories by taking into account the instruments' analytical concepts, technical features and environmental requirements, as well as results of major validation studies. Sources: Data on technical features of selected portable instruments were mainly extracted from manufacturers' websites. Information on validation studies of various molecular assays developed for the selected instruments was extracted from peer-reviewed publications searched for through PubMed. Content: Eight portable diagnostic molecular instruments (Alere q, GeneXpert Edge, GeneXpert Omni, Genedrive, PanNAT, Revogene, cobas Liat and ID Now) that are commercially available or in the launching stage are presented and evaluated in the context of the mobile microbiology concept, with particular emphasis on technical features and environmental requirements. Both the cobas Liat and the Alere i assays have been extensively validated in a variety of studies carried out in both adult and paediatric patients from various settings (ranging from primary care to emergency care departments in tertiary centres). Most studies showed comparable performance of cobas Liat and Alere i molecular assays with the standard-of-care in vitro diagnostics molecular assays routinely performed in dedicated/centralized molecular diagnostics laboratories. In addition, acceptable performance of Alere q and Genedrive instruments has been shown in implementations studies for early infant diagnosis of children born to human immunodeficiency virus-positive mothers and detection of hepatitis C virus RNA, respectively. Additional validation studies on existing (GeneXpert Edge, PanNAT, Revogene) and emerging (GeneXpert Omni) technologies are warranted. Implications: Several portable molecular diagnostic platforms reviewed are suitable for mobile microbiology applications. Further development in this field should be directed toward providing a broader range of assays per instrument, multiplexing, reducing the frequency of invalid results, and price cutting.